Vernacularisation of Sufism in the Balkans: The Example of the ‘Shpija e Zotit’ (House of God) Treatise - Xhafçe, Zeqije; Rexhepi, Abdulla (Universitas Islam Negeri Mataram, 2024)
Sufism, beyond being a philosophical discipline, is a way of life to enhance individual and societal existence. The concrete product of the intellectual and spiritual effort shown in Sufism has often emerged in poetry or prose. This study examines a Sufi manuscript as a form of Sufi legacy that significantly influenced the Muslim Albanian community in Ottoman territories. The focus is on the treatise